Conceptualizing Consent: Cross-national and Temporal Representations of Sexual Consent in Young Africans' Creative Narratives on HIV. Issue 9 (22nd November 2021) - Singleton, Robyn; Obong'o, Chris; Mbakwem, Benjamin Chigozie; Sabben, Gaelle; Winskell, Kate
ABSTRACT: Sexual violence, comprising all non-consensual sexual acts, is an important driver of HIV infection in sub-Saharan Africa. Definitions of sexual violence rely on understandings of sexual consent, understood as a feeling of willingness that is communicated via shared indicators of consent. In this paper, through analysis of young authors' narrative-based social representations, we sought to provide insight into young Africans' sense-making around sexual consent in order to develop a conceptual framework that can guide future methodological and conceptual work. We analyzed representations of sexual consent in a sample of 291 creative narratives about HIV written for a scriptwriting competition by young Nigerians, Kenyans and Swazis in 2005, 2008, and 2014. We combined thematic data analysis and narrative-based approaches. Narratives represented consent as a feeling of wanting or being willing to have sex, or an intention to have sex, communicated via character actions, conversations, or circumstances. Some narratives depicted characters not wanting but consenting to sex to avoid negative repercussions. Representations of sexual consent were fairly consistent across contexts and over time, although certain representations were more prominent in some country/year samples than others. Results are translated into a conceptual framework that can guide future prevention efforts to reframe sexual consent.